ANALISIS GROWTH RATIO, RASIO EFEKTIVITAS DAN EFISIENSI PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MEDAN - Azizah Widyastuti Harahap; Mas’ut .; Jalilah Ilmiha; Syamsul Effendi (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
The definition of the financial performance of a region is the level of achievement of a work result in the regional financial sector. Measurement of the financial performance of local governments is carried out by examining the regional financial performance ratios as seen through the Medan City Regional Budget Realization Report. The ratios to assess the financial performance of local governments used in this study include: Growth Ratios, Effectiveness and Efficiency Ratios. This study aims to analyze the level of growth ratios, effectiveness and efficiency during the 2016-2019 period to see the financial performance of the Medan City Government. In writing this thesis using quantitative descriptive analysis method. The results of this study indicate that the financial performance of the Medan City Government by using a Growth Ratio is still not optimal because there was a significant decrease in 2018 due to a decrease in regional income in Medan City. The financial performance of Medan City as measured by the 2016 Effectiveness Ratio is categorized as quite effective, namely 84.82%. In 2017, 2018, and 2019 were categorized as effective because they had a value above 90%, namely 2017 amounting to 99.15%, 2018 amounting to 92.88%, and in 2019 amounting to 90.56%. The financial performance of Medan City Government as measured by the Efficiency Ratio is categorized as very efficient because all results have a value below 60%. 2016 10.35%, 2017 8.55%, 2018 7.35%, 2019 9.61%.